2019
DOI: 10.1038/s41529-019-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and corrosion evolution of additively manufactured aluminium alloy AA7075 as a function of ageing

Abstract: Additively manufactured high strength aluminium (Al) alloy AA7075 was prepared using selective laser melting (SLM). High strength Al-alloys prepared by SLM have not been widely studied to date. The evolution of microstructure and hardness, with the attendant corrosion, were investigated. Additively manufactured AA7075 was investigated both in the "as-produced" condition and as a function of artificial ageing. The microstructure of specimens prepared was studied using electron microscopy.Production of AA7075 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Nevertheless, aluminum alloys have low density and high strength, making this material the most used structural material with iron and steel [66]. Moreover, when processed, some alloys can present a better corrosion resistance than the wrought [67]. The majority of the alloys used in PBF-LB are based on commercial grade alloys [66].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, aluminum alloys have low density and high strength, making this material the most used structural material with iron and steel [66]. Moreover, when processed, some alloys can present a better corrosion resistance than the wrought [67]. The majority of the alloys used in PBF-LB are based on commercial grade alloys [66].…”
Section: Methodsmentioning
confidence: 99%
“…Pits formed in SLM produced AA7075 after corrosion tests were remarkably smaller in comparison to those upon wrought AA7075-T6 due to its finer microstructural features and the absence of large constituent particles. In the as-built AA7075 condition, pits were more pronounced along melt pool boundaries, while they were uniformly distributed in the solutionized sample, and the following ageing caused larger pits along grain boundaries than those within grains [291] The EBM technology offers unique features that other additive manufacturing technologies or even traditional manufacturing methods cannot offer. One of these is the in-process heat treatment capability through the utilization of the elevated build temperature and precise melt pool temperature control.…”
Section: Corrosion Behavior Of Powder Bed Fusion Additive Manufactured Al Alloysmentioning
confidence: 99%
“…Another study worked to prepare crack-free 7xxx Al alloys through co-incorporation of submicron Si and TiB2 into the alloys [290]. Gharbi et al [291] reported the microstructure of as-SLMed AA7075 containing the quasi-crystalline phase (ν-phase) as the principal nano-structural feature. Solution heat treatment dissolved the quasi-crystalline ν-phase and ageing led to precipitation of η -phase (MgZn 2 ) within grains and along grain boundaries, revealing columnar grains in the microstructure of AA7075 alloy.…”
Section: Laser-processed Al Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other examples of microstructural features and processing defects that have been investigated are; nanoscale oxides/inclusions 7,20,23,24 , solute segregation (i.e. cell boundaries, melt pool boundaries) 7,13,[22][23][24][25][26][27][28][29] , texture and grain character 29 , residual stresses 3,30,31 , surface roughness 18,20,[32][33][34][35] , and porosity 7,9,[18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%